Caballero inexistente - Calvino, Italo; Calvo Montoro, María J. (María Josefa); Benítez, Esther; Calvino, Italo (Madrid : Siruela, 2012)
Recounts the chivalrous exploits of an empty suit of armor and the separate halves of a nobleman who has been bisected by a cannon ball.
Online resource; title from ePub title page (Digitalia, viewed March 12, 2016)
Keywords: Electronic books